EFEKTIVITAS DALAM IMPLEMENTASI KURIKULUM SEKOLAH DI MA AL-AMIN - Rohmah, Siti; Trimulyo, Joko; Kurniawan, Dede Irwan (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2023)
Implementation of the curriculum is the translation of the document curriculum into a curriculum as an activity or reality. Curriculum implementation is realized in the form of learning experiences with principles that make it easier and more effective to be communicated to various parties such as school leaders, educators, school supervisors, and other support staff. The method and type of this research are interviews, observations of related parties. The findings in this study are: 1) Implementation of an effective curriculum has the principles of: (a) obtaining equal opportunities, (b) child-centered, (c) approaches and partnerships, (d) unity in policy and diversity in implementation. 2) Stages of Curriculum Implementation, namely: (a) planning, (b) implementation, and (c) evaluation. 3) The factors that influence the implementation of the curriculum are: (a) planning, (b) substance (content) of the curriculum, (c) educators, (d) school climate and culture, (e) facilities and infrastructure, (f) the role of the head school. 4) Model of curriculum implementation, including: (a) Concern-Based Adoption Model (CBAM), b) The Innovation Profile Model, and c) TORI Model (Trust, Opening, Reallization and Independence